Quality of life for quality of work life: an historical and practical rescue - Rodriguez, Sandra Yvonne Spiendler; Sauer, Graziela Calvi (Revista de Psicologia da IMED, 2014)
This study analyzes with the aid of literature, the historical evolution of the meaning associated to the Quality of Work Life (QWL) as well as the practice of QWL in the organizational context. For this, the VHL and SciELO Brazil databases and data collections that deal with this subject in the libraries of the Faculdade de Desenvolvimento do Rio Grande do Sul ( FADERGS ) and the Universidade Federal do Rio Grande do Sul ( UFRGS ) were consulted . Discusses the gaps to be satisfied as to the evolution of the QWL,  and that by the lack of interventions of QWL in organizations, the practical implications are a challenge and an opportunity for new researchers. There is also the difficulty in obtaining a parameterization of the concept of QWL, considering its subjective, complex and multidimensional.